Experimental demonstration of anomalous Floquet topological insulator for sound - Yu-Gui Peng (Nature Portfolio, 2016)
Topological protected acoustic wave propagation has been predicted, but yet awaits for experimental demonstration. Here, Peng et al. report one-way propagation of pseudo-spin-dependent edge states for sound, analogous to Floquet topological insulator in solid state.